Red date scale, Phoenicococcus marlatti (Cockerell) (Insecta: Hemiptera: Phoenicoccidae) - Adriana Espinosa; Amanda Hodges; Gregg Hodges; Catharine Mannion (EDIS, 2009)
EENY-454, a 4-page illustrated fact sheet by Adriana Espinosa, Amanda Hodges, Greg Hodges, and Catharine Mannion, is part of the Featured Creatures collection. It describes this most important pest of the date palm, its distribution, field characteristics, life cycle, hosts, general plant damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.